Bone tool and tuber processing: A multi-proxy approach at Boyo Paso 2, Argentina - Medina, Matias Eduardo (2018)
This article provides results from a full morphological, use-wear and microfossil residue analysis of a notched bone tool made from a camelid scapula, which was recovered from the late pre-Hispanic site of Boyo Paso 2 (1500-750 years BP, Sierras of Córdoba, Argentina). The use-wear pattern showed striations similar to those recorded in experimental bone tools used for scraping activities. The starch grains found on the active or working edge are similar to the Andean tuber crop Oxalis tuberosa, and suggest that the tool was used for peeling wild or domesticated Oxalis sp. tubers, thereby questioning the disproportionate attention directed towards maize in late pre-Hispanic economies.